The origin of stars - Smith, Michael D. (Michael David), 1955- (Imperial College Press, 2004)
Where do stars come from and how do they form? These are profound questions which link the nature of our Universe to the roots of mankind. Yet, until a recent revolution in understanding, the proposed answers have been raw speculation. Now, accompanying penetrating observations, a new picture has come into prominence. This book presents the latest astounding observations and scientific ideas covering star formation, star birth and early development. It encompasses all aspects, from the dramatic stories of individual objects, to the collective influence of entire stellar systems. The very first stars to come into existence and the nurturing of planets are discussed to provide the reader with a comprehensive overview. Presenting background information with only the essential mathematics, this book will appeal to scientists wishing to expand their horizons, students seeking solid foundations, and general readers with enquiring minds.